Pro Access 2010 development - Collins, Mark (Apress Imprint: Apress, 2011)
Pro Access 2010 Development is a fundamental resource for developing business applications that take advantage of the features of Access 2010 and the many sources of data available to your business. In this book, you'll learn how to build database applications, create Web-based databases, develop macros and Visual Basic for Applications (VBA) tools for Access applications, integrate Access with SharePoint and other business systems, and much more. Using a practical, hands-on approach, this book will take you through all the facets of developing Access-based solutions, such as data modeling, complex form development, and user interface customizations. You'll then deploy your solution to the web and integrate it with other external data sources. This book is full of handy tricks to help you get the most out of what Access has to offer, including its comprehensive set of features and tools for collecting, using, and acting on business data, whether your data is in Access or stored on another platform. You'll also see how to smoothly integrate your applications with SQL Server databases and other Office programs, such as Outlook.